A EXPANSÃO DA FRONTEIRA AGRÍCOLA NUM CENÁRIO DE GLOBALIZAÇÃO DA AGRICULTURA - Benjamin Alvino de Mesquita (Revista de Políticas Públicas, 2018)
Large-scale commodity production, marketing and export under the control of large corporations, both past and present, has always been present in peripheral areas of capital, such as Latin America, Africa, or Australia. In the last decades due to the liberalizing policies, there was an offensive in the expansion of these oligopolistic groups in the agricultural frontier of these areas, with government support.The expectation of new investments in these places was that it would bring economic growth and employment on the occupied agricultural frontier. However, the increased exposure of local markets to state-led international competition has disrupted whole sectors and expropriated millions of small producers. In Brazil, the presence of capital in the production of commodities is striking (exports) and frustrating, due to the socioeconomic results of employment, tax, disarticulation of the peasants in the environment where they are. The billions of dollars exported by the global companies of the sector do not transfer only wealth abroad, it also transfers a whole legacy of devastation and poverty to the future generations present there.